PENGARUH DEBIT ALIRAN RESIN BISPHENOL A LP-1Q-EX PADA METODE VACUUM INFUSION RESIN TERHADAP KEKUATAN TARIK KOMPOSIT SERAT KULIT POHON WARU (HIBISCUS TILIACEUS) - teddy wicaksono wicaksono; Akhmad Farid; Nova Risdiyanto Ismail; Arief Rizki Fadhillah (Jurnal Energi dan Teknologi Manufaktur, 2021)
Research on natural fiber composites is being carried out in various parts of the world to produce solutions to environmental problems by utilizing natural fiber materials prepared for environmentally friendly and renewable materials. The natural fiber currently being developed for composite reinforcement is hibiscus bark fiber. This study aims to determine the effect of the flow rate of bisphenol A resin LP-1Q-EX on the vacuum infusion resin method on the tensile strength of hibiscus bark fiber composites. The method used in this study is the fiber structure model in the direction of tensile load, composite using hibiscus bark fiber (Hibiscus tiliaceus), composite using bisphenol A resin LP-1Q-EX, composite using mass fraction with a ratio of 60 fibers: 40 resin, Waru tree bark was treated with 6% NaOH alkaline soaking (aquades 938.8 grams, and NaOH 61.2 grams) for 120 minutes, the number of hibiscus tiliaceus bark fibers in one composite material was 22 fibers with a material thickness of 3.2 mm (according to ASTM D638-03 Type 1 standard), the composite was produced using the vacuum infusion resin method with variations in resin flow rate of 1.19 ml/s, 3.66 ml/s, 4.67 ml/s. The testing process in this study is a composite tensile test using the ASTM D638-03 Type I standard. The analysis of the fractures that occur in each specimen uses macro photos, namely the process of taking several photos of the fracture after the specimen is subjected to a tensile test using a digital camera placed on the ground. topped a tripod. The results of the composite tensile test showed that the variation of resin flow rate of 1.19 ml/s had the lowest tensile strength of 282.94 MPa, while the variation of flow discharge of 3.66 ml/s had the highest tensile strength of 301.75 MPa. and the flow variation of 4.67 ml/s has a tensile strength of 284.54 MPa. Based on the results of the tensile test of the hibiscus tiliaceus bark fiber composite using the vacuum infusion resin method, the highest strength was obtained at a variation of the resin flow rate of 3.66 ml/s.